Analysis of the use of libraries, physical and digital, by engineering students of the Autonomous University of Nuevo León - Cantú Mata, José Luis; Arias Coello, Alicia; Estrada Domínguez, Jesús Eduardo; Simón Martín, José; Segoviano Hernández, José; Banda Muñoz, Fernando (Revista General de Información y Documentación, 2021)
The purpose of the study is to know the information search strategies of the students of the engineering area of ​​the University of Nuevo León, as well as their informative behaviors, motivations and desires. A measuring instrument applied randomly in the sample has been used to perform the corresponding validation and analysis, using structural equations using the exploratory factor analysis technique, which allows separating the relationships of the variables for each set of dependent variables, as presented in the model. The data were processed in the statistical packages SPSS and SMART-PLS. The results show an inverse relationship, which indicates that the digital collection is not considered as a means of searching and gathering information; therefore, it does not offer adequate performance, possibly because teachers’ recommendations are not oriented towards the use of the digital library.